(untitled) - Elliotte Rusty Harold (Cambridge, 1997)
Why Networked java; Basic Network concepts; Basic web concepts; Processing internet addresses; Retrieving data with URLs; The network methods of java applet.Applet; Sockets for clients; Sockets for servers; UDP datagrams and sockets; The URL connection class; Protocol handlers...
Lập trình mạng
Keywords: computer networks - the united states,java